Genomics and the Making of Yeast Biodiversity - Hittinger, Chris Todd (2015)
Yeasts are unicellular fungi that do not form fruiting bodies.Although the yeast lifestyle has evolved multiple times, mostknown species belong to the subphylum Saccharomycotina(syn. Hemiascomycota, hereafter yeasts). This diverse groupincludes the premier eukaryotic model system,Saccharomyces cerevisiae; the common human commensaland opportunistic pathogen, Candida albicans; and over1000 other known species (with more continuing to bediscovered). Yeasts are found in every biome and continent andare more genetically diverse than angiosperms or chordates.Ease of culture, simple life cycles, and small genomes (10?20 Mbp) have made yeasts exceptional models for moleculargenetics, biotechnology, and evolutionary genomics. Herewe discuss recent developments in understanding thegenomic underpinnings of the making of yeast biodiversity,comparing and contrasting natural and human-associatedevolutionary processes. Only a tiny fraction of yeastbiodiversity and metabolic capabilities has been tapped byindustry and science. Expanding the taxonomic breadth ofdeep genomic investigations will further illuminate how genomefunction evolves to encode their diverse metabolisms andecologies.